Dampak Game Online Mobile Legends: Bang Bang terhadap Mahasiswa - Devita Rani; Effiati Juliana Hasibuan; Rehia K. Isabela Barus (PERSPEKTIF, 2018)
Mobile   Legends   Online   Games:   Bang   Bang   is   one   manifestation   of   technological development in new media. The purpose of this study was to find out how the positive and negative impact of playing Mobile Legends: Bang Bang online games to FISIP UMA students who play games. The theory used in this study is communication, new media, positive and negative online games. The method used is a qualitative method. Where the informants fifth in FISIP UMA students. Data collection techniques are carried out by means of participatory observation, in-depth interviews and documentary evidence. The result of the study show that the impact of playing Mobile Legends is influenced by the attitude of the players, indifferent to the social environment, wasteful in terms of time and economy, can get new friends in cyberspace from other countries so as not to limit interaction, add insight and experience about technology.